Accounting for the uncertain effects of hydraulic interactions in optimising embankments heights: Proof of principle for the IJssel River. (29th April 2019) - Ciullo, Alessio; de Bruijn, Karin M.; Kwakkel, Jan H.; Klijn, Frans
Abstract: Most alluvial plains in the world are protected by flood defences, for example, embankments, whose primary aim is to reduce the probability of flooding of the protected areas. At the same time, however, the presence of embankments at one area influences hydraulic conditions of downstream areas located on the same river. These hydraulic interactions are often neglected in current flood risk management. The aim of this study is to explicitly acknowledge hydraulic interactions and investigate their impact on establishing optimal embankment heights along a stretch of the IJssel River. We find that the current approach leads to a single solution, while taking into account hydraulic interactions substantially expands the number of promising solutions. Furthermore, under a reference scenario, the current approach is in fact suboptimal with respect to both downstream locations and the system as a whole. Under uncertainty, it performs adequately from a system viewpoint, but poorly for individual locations, mostly due to risk overestimation downstream. Overall, the current approach proves to be too short‐sighted, because spatial trade‐offs among locations are neglected and alternative solutions remain hidden. Acknowledging the effect of hydraulic interactions provides policy makers with a broader and more comprehensive spectrum of flood risk management strategies.